Therapeutic effect of neoadjuvant chemotherapy combined with curettage to treat distal femoral osteosarcoma: A case report. Issue 46 (November 2017) - Lai, Qi; Ye, Conglin; Gao, Tian; Xiao, Jun; Xie, An; Liu, Xuqiang; Yu, Xiaolong; Liu, Jun; Dai, Min; Liu, Hucheng; Zhang, Bin
Abstract: Rationale: Osteosarcoma is the most common malignant bone tumor in children and adolescents. Metastasis occurs early, the mortality rate is high, and the tumor results in a tremendous physical, mental, and economic burden on patients. Therefore, the treatment of osteosarcoma has been important for orthopedic surgeons. However, treatment has always been a difficult problem globally. Patient concern: We present the case of a 22-year-old girl with increasing local pain in the distal left thigh. Diagnoses: The patient was initially diagnosed as bone cancer according to computed tomography (CT) and X-ray imaging. And the patient was further diagnosed as osteosarcoma via to puncture biopsy of the left distal femur. Interventions: Local arterial infusion chemotherapy, systemic intravenous chemotherapy, and curettage was conducted because of limb salvage program. Outcomes: The patient was doing well with no evidence of local or distant recurrence 7 years after the surgery. Lessons: Our case indicated that limb osteosarcoma patients can undergo a limb salvage program of local arterial infusion chemotherapy, systemic intravenous chemotherapy, and curettage.